122OShould transarterial chemoembolization be continued after non-response to the first two sessions for intermediate-stage hepatocellular carcinoma?. (24th November 2019) - Chen, S; Peng, Z; Chen, M; Feng, S-T; Kuang, M
Abstract: Background: Current guidelines recommend that two transarterial chemoembolization (TACE) should be performed before switching to another treatment for intermediate-stage HCC, but without robust evidence. Considering the paucity of effective subsequent treatments after TACE-refractoriness, we aimed to evaluate radiologic response of HCC to the third TACE (TACE-3) after nonresponse (stable disease (SD) or progressive disease (PD)) to the first two sessions, and to establish a nomogram to predict responders to TACE-3. Methods: The study enrolled 1672 intermediate-stage HCC patients with Child-pugh A liver function (training cohort: n = 918; internal validation cohort: n = 460; external validation cohort: n = 294) who did not respond to (based on mRECIST) the first two TACE but underwent ≥3 consecutive TACE from three centers. Radiologic response rate to TACE-3 and its correlation with overall survival (OS) was evaluated. Nomogram predicting responders to TACE-3 was established and validated. Results: For patients with SD after the first two TACE, the response rate after TACE-3 was 44.4% in training and internal validation cohorts and 51.5% in external validation cohort. For patients with PD, corresponding rates were 2.7% and 2.2%. Responders to TACE-3 achieved higher 5-year OS rates than non-responders in three cohorts (all P < 0.001). Radiologic response to TACE-3 (HR = 0.151, 95% CI: 0.117-0.195, P < 0.001) was the strongest prognostic factor of OS. The C-index of nomogram, constructed by tumor size, tumor capsule and alpha-fetoprotein, was 0.835 (95% CI: 0.810, 0.861) in training cohort, 0.853 (95% CI: 0.819, 0.887) in internal validation cohort and 0.846 (95% CI: 0.825, 0.892) in external validation cohort. Conclusions: Approximately 50% of patients with SD could respond to TACE-3 with improved survival whereas patients with PD barely could. Our nomogram is effective in predicting responders to TACE-3. Legal entity responsible for the study: The First Affiliated Hospital of Sun Yat-sen University. Funding: The National Natural Science Foundation of China (No. 81801703), the Guangdong Natural Science Foundation of Guangdong Province (No. 2018A030310282), the National high level talents special support plan–"Ten thousand plan"–Young top-notch talent support program, the National Science Fund for Distinguished Young Scholars (No. 81825013). Disclosure: All authors have declared no conflicts of interest.